2016
DOI: 10.2113/econgeo.111.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Gold and Pyrite at the Xincheng Gold Deposit, Jiaodong Peninsula, China: Implications for Gold Source and Deposition in a Brittle Epizonal Environment

Abstract: The Xincheng gold deposit, hosted by the Early Cretaceous 132 to 123 Ma Guojialing-type granitoids in northwest Jiaodong Peninsula, southeast North China craton, formed about 2 billion years later than regional metamorphism of the Archean Jiaodong basement rocks. The Xincheng deposit comprises mineralized zones with three types of hydrothermal pyrite associated with gold, tellurides, and a variety of sulfides: py1 as disseminated euhedral to subhedral grains in altered granitoids around quartz veins; py2 as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 217 publications
(98 citation statements)
references
References 61 publications
1
97
0
Order By: Relevance
“…(a) Calculated maximum principal stress fields (compression), pre‐130 Ma and pre‐gold mineralization, and (b) minimum principal stress fields for WNW extensional event post‐120 Ma and post‐gold mineralization. Geological map compiled by Lu et al (), L. Q. Yang et al (), and L. Q. Yang, Deng, Wang, Guo, et al (). Palaeostress directions derived from Y. Q. Zhang et al (); Y. Q. Zhang, Li, et al (); T. Zhang and Zhang (); Ren et al (); L. Zhang (); and Charles et al () [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Structural Setting Prior To Gold Mineralization Eventmentioning
confidence: 99%
See 3 more Smart Citations
“…(a) Calculated maximum principal stress fields (compression), pre‐130 Ma and pre‐gold mineralization, and (b) minimum principal stress fields for WNW extensional event post‐120 Ma and post‐gold mineralization. Geological map compiled by Lu et al (), L. Q. Yang et al (), and L. Q. Yang, Deng, Wang, Guo, et al (). Palaeostress directions derived from Y. Q. Zhang et al (); Y. Q. Zhang, Li, et al (); T. Zhang and Zhang (); Ren et al (); L. Zhang (); and Charles et al () [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Structural Setting Prior To Gold Mineralization Eventmentioning
confidence: 99%
“…The Linglong and Taishang gold deposits are situated at the northern segment of the Zhaoping Fault. Modified from L. Q. Yang, Deng, Wang, Guo, et al (). (b) Sketch map of the disseminated/microbreccia‐stockwork orebody and fault zones at the Taishang gold deposit, showing the structural control of the intersection of the Poutouqing Fault and the E–W‐trending faults on gold mineralization and hydrothermal alteration.…”
Section: Regional Structural Controls On Gold Mineralizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cook et al (2013) indicated that there may be continuous fluid flux through preexisting pyrite grains, promoting ongoing sulfur liberation and allowing Au precipitation. However, it is unlikely that this process could generate a significant amount of Au (Yang et al, 2016). There should be a mechanism to precipitate the visible Au and further studies should be carried out to determine if the Au in Gangcha gold deposit is present in native form.…”
Section: Trace Element Distribution In Pyritementioning
confidence: 99%